Brief Report: Enhanced Normalization of CD4/CD8 Ratio With Earlier Antiretroviral Therapy at Primary HIV Infection. (1st September 2016) - Thornhill, John; Inshaw, Jamie; Kaleebu, Pontiano; Cooper, David; Ramjee, Gita; Schechter, Mauro; Tambussi, Giuseppe; Fox, Julie; Samuel, Miriam; Miro, Jose M.; Weber, Jonathan; Porter, Kholoud; et al.
Abstract : Background: Total CD4 + T-cell counts predict HIV disease progression but do not necessarily reflect normalization of immune function. CD4/CD8 ratio is a marker of immune dysfunction, a prognostic indicator for non-AIDS mortality, and reflects viral reservoir size. Despite antiretroviral therapy (ART), recovery of CD4/CD8 ratio in chronic HIV infection is incomplete; we hypothesize enhanced CD4/CD8 ratio recovery with earlier treatment initiation in recently infected individuals. Methods: CD4 + count and CD4/CD8 ratio were analyzed using data from 2 cohorts: SPARTAC trial and the UK HIV Seroconverters Cohort where primary HIV infection (PHI) was defined as within 6 months from estimated date of infection. Using time-to-event methods and Cox proportional hazard models, we examined the effect of CD4/CD8 ratio at seroconversion on disease progression (CD4 <350 cells per cubic millimeter/ART initiation) and factors associated with time from ART initiation to CD4/CD8 normalization (ratio >1.0). Findings: Of 573 seroconverters, 482 (84%) had abnormal CD4/CD8 ratios at HIV seroconversion. Individuals with higher CD4/CD8 ratio at seroconversion were significantly less likely to reach the disease progression endpoint [adjusted hazard ratio (aHR) (95% CI) = 0.52 (0.32 to 0.82), P = 0.005]. The longer the interval between seroconversion and ART initiation [HR (95% CI) = 0.98 per month increase (0.97, 0.99), P < 0.001], the less likely the CD4/CD8 ratio normalization. ART initiation within 6 months from seroconversion was significantly more likely to normalize [HR (95% CI) = 2.47 (1.67 to 3.67), P < 0.001] than those initiating later. Interpretation: Most individuals presenting in PHI have abnormal CD4/CD8 ratios. The sooner the ART is initiated in PHI, the greater the probability of achieving normal CD4/CD8 ratio. Abstract : Supplemental Digital Content is Available in the Text.